Inclusión de harina de algarrobo (Prosopis chilensis) en la alimentación de cerdos postdestete y efecto en los parámetros productivos - Bazurto Carranza, José Alejandro (2022)
The present work consisted of evaluating the inclusion of carob (Prosopis chilensis) meal in the feeding of post-weaning pigs from 35 to 80 days of age and its effect on the productive parameters. Twelve Landrace x Pietrain pigs were assigned to a DCA, with 3 treatments (T0: Control treatment; T1 inclusion of 5% carob flour and T2 inclusion of 15% carob flour) and 4 repetitions. An analysis of variance was performed on the data of the productive indicator variables and it was found that there were no significant differences between the treatments; the information was processed with the statistical package InfoStat (2019). However, T2 obtained a weekly weight of (44.51 kg ± 0.07), which stood out over the other treatments; the accumulated weekly weight gain and feed conversion were significant at T0 with (31.60 kg ± 0.17) and (1.45) respectively; T1 prevailed in food consumption (46.15 kg ± 0.13). Cortisol levels were reported increased in T1 (71.68 ug/dL ± 2.13). In the cost/benefit analysis, higher income was found in animals that did not include carob flour T0, in which for each dollar invested a profit of $0.24 was made. It is concluded that the feeding of post-weaning pigs with the inclusion of carob flour in the feed did not disadvantage the productive variables of the supplied diets, it did not affect animal health and welfare, although the economic benefit was lower.